Design and Analysis of Partitioned Square Loop Antennas - Hasse, R.; Hunsicker, W.; Kajfez, D.; Elsherbeni, A.; Demir, V. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A novel antenna design is presented for operation at 5.8 GHz with omni-directional pattern characteristics. The antenna employs square loop geometry of one wavelength perimeter. The loop is partitioned with capacitive elements in order to minimize phase variations in the current flow and thereby enhance the radiation efficiency. Five capacitive elements are used to achieve optimal loop current flow, resulting in phase variations smaller than ± 6°. The performance of the antenna is first analyzed with a thin-wire antenna using method of moments (MoM) solver and later validated using a custom finite difference time domain (FDTD) package. The calculated radiation pattern in the plane of the loop is close to omni-directional with directive gain of 1.5 dBi. A printed circuit antenna is manufactured with alternating top- and bottom-layer conductors, with the overlapped regions acting as physical capacitors. The measured radiation patterns of the printed antenna confirm the predicted omni-directional behavior in the equatorial plane, while the input impedance demonstrates a close match to 50 Ω. The mean value of the gain is 2.15 dB at 5.869 GHz. A second printed antenna, having toplayer conductors only and gap capacitors, is simulated using finite element (FEM) software, and the performance is nearly omni-directional with a directive gain of 1.66 dBi. Both designs are very sensitive to the dimensions of the physical capacitors and require a highly accurate method of fabrication.